TEORI KONSUMSI DAN PRODUKSI DALAM PERSPEKTIF EKONOMI ISLAM - Sri Wahyuni (AKUNTABEL, 2013)
Consumption is defined as fulfilling the needs of goods and services that give ones virtue (maslahah) both in life and after. In general this fulfillment will provide additional benefits in term of physical, spiritual, intellectual, or material, as well as satisfaction for the doers. Fulfilling the needs will enhance its value and happiness. However, if it is not done based on willingness it will bring benefit and satisfaction only. In Islam,production process should be done according to ethics and norms (shar’i) and gives benefits for the people besides the producers themselves. Production should be utilized in proper way considering the usefulness for the world and the responsibility of being human as the leader upon earth (KhalifatulfilArdh)Keyword: consumer theory, production theory, needs, desires, and welfare